Estudo clínico-laboratorial para verificar e comparar eficácia e segurança do ácido retinoico a 0,05% em creme e a 5% em peelings superficiais no fotoenvelhecimento e carcinogênese do antebraço - Sumita, Juliana Mayumi [UNIFESP] (2017)
Background: Topical use of retinoic acid in cream is the gold standard treatment for skin aging, particularly photoaging. To obtain the same results in less time, the peeling of retinoic acid was created, but there are few controlled studies on its effectiveness, limited to the improvement of the signs of photoaging and cutaneous hyperpigmentation. Objectives: Evaluate and compare efficacy and safety of retinoic acid at 0.05% and 5% (as a peeling agent) for photoaging and carcinogenesis of the forearm. Methods: Prospective clinical study of therapeutic intervention, randomized, comparative and evaluator blinded. Efficacy and safety evaluated by the participant's opinion, severity of photoaging, measurement of the viscoelastic properties of the skin, corneometry, profilometry, high frequency ultrasound, histological exams (Hematoxylin-Eosin and Verhoeff stainings) and immunohistochemistry (p53, bcl-2 , Ki67 and collagen I). Results: The two forearms of 24 participants were evaluated. Three efficacy parameters showed opposite effects of the two treatments. 1) The thickness of the stratum corneum decreased with 0.05% retinoic acid and increased with 5%. 2) The echogenicity of the dermis by ultrasonography increased with 0.05% and decreased with 5%. 3) Ki67 expression increased with 0.05% and decreased with 5%. The favorable opinion of the participant, improvement of the photoaging score, corneometry, profilometry, recovery of viscoelasticity, increase of papillary dermis thickness, reduction of solar elastosis, decrease of p53, increase of bcl-2 and collagen I were not different between them. There was good tolerability in both treatments. Conclusion: The results confirmed the safety and benefits of retinoic acid at 0.05% and 5%, but at different scopes. 0.05% retinoic acid reversed the signs of photoaging in the long term (elevation of the echogenicity of the dermis), reaffirming itself as a gold standard for the treatment of photoaging. Peeling of 5% retinoic acid reduced the risk of skin cancer in the short term (reduction of Ki67), and was shown as a promising method for adjuvant treatment of actinic keratoses and cancerization field.